Characterization of circular RNA transcriptomes in psoriasis and atopic dermatitis reveals disease‐specific expression profiles. Issue 8 (16th November 2020) - Moldovan, Liviu I.; Tsoi, Lam C.; Ranjitha, Uppala; Hager, Henrik; Weidinger, Stephen; Gudjonsson, Johann E.; Kjems, Jørgen; Kristensen, Lasse S.
Abstract: Atopic dermatitis (AD) and psoriasis are two common chronic inflammatory skin diseases that are associated with various comorbidities. Circular RNA (circRNA) constitutes a major class of non‐coding RNAs that have been implicated in many human diseases, although their potential involvement in inflammatory skin diseases remains elusive. Here, we compare and contrast the circRNA expression landscapes in paired lesional and non‐lesional skin from psoriasis and AD patients relative to skin from unaffected individuals using high‐depth RNA‐seq data. CircRNAs and their cognate linear transcripts were quantified using the circRNA detection algorithm, CIRI2, and in situ hybridization and Sanger sequencing was used for validation purposes. We identified 39, 286 circRNAs among all samples and found that psoriasis and AD lesional skin could be distinguished from non‐lesional and healthy skin based on circRNA expression landscapes. In general, circRNAs were less abundant in lesional relative to non‐lesional and healthy skin. Differential expression analyses revealed many significantly downregulated circRNAs, mainly in psoriasis lesional skin, and a strong correlation between psoriasis and AD‐related circRNA expression changes was observed. Two individual circRNAs, ciRS‐7 (also known as CDR1as) and circZRANB1, were specifically dysregulated in psoriasis and show promise as biomarkers for discriminating AD from psoriasis. In conclusion, the circRNA transcriptomes of psoriasis and AD share expression features, including a global downregulation relative to healthy skin, but this is most pronounced in psoriasis, and only psoriasis is characterized by several circRNAs being dysregulated independently of their cognate linear transcripts. Finally, specific circRNAs could potentially be used to distinguish AD from psoriasis.